The Creative Animal How Every Animal Builds its Own Existence - Marchesini, Roberto (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book deals with the theme of creativity in the animal world, conceived as a basic function for adapting to specific situations and as a source of innovations and inventions. Creativity is a fundamental resource for the individual who always has a leading role in conduct. To explain creativity, the book focuses on the concept of animal subjectivity, providing a new explanatory model of behavior capable of overcoming the image of the animal moved by automatisms. This model does not use consciousness as a necessary condition, but is based: 1) on affective components, such as behavioral motives, and 2) cognitive, as tools used by the subject to carry out his purposes. Particular attention is paid to the learning processes showing the subjective character of the experience. One topic addressed is the role of creativity in the evolution of living beings: how an invention, by modifying the niche characteristics, is able to change the selective pressures and the trajectory of phylogeny. Roberto Marchesini explains that creativity is a factor that is anything but rare or exceptional in the animal world-it constitutes a fundamental quality for many aspects of animal life.
Chapter 1 - In praise of improvisation -- Chapter 2 - On subjectivity -- Chapter 3 - Having interests to defend -- Chapter 4 - It is not possible to just repeat -- Chapter 5 - Equipment as tools to be used -- Chapter 6 - Perceiving means building -- Chapter 7 - Build your niche and address phylogeny -- Chapter 8 - It is not always anthropomorphism -- Chapter 9 - Leadership in learning -- Chapter 10 - Plural intelligences -- Chapter 11 - The inevitable lightness of culture -- Chapter 12 - All colors of consciousness.
Keywords: Animal welfare-Moral and ethical aspects; Cognition in animals; Ethnology; Animal Ethics; Animal Cognition; Ethnology